2022
DOI: 10.1038/s41380-022-01793-3
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the genetic architecture of broad antisocial behavior through a genome-wide association study meta-analysis

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 97 publications
1
28
0
Order By: Relevance
“…As a result, we included summary statistics from GWAS capturing a variety of parental risk factors for conduct problems in the domains of psychiatric conditions, substance use/abuse, cognitive and education-related factors, or other parental risk factors that could underlie potential genetic nurture effects (Table S2). Specifically, we used summary statistics for GWAS on ADHD (40), depression (41), anxiety disorders (42), antisocial behaviour (ASB) (43), lifetime smoking (44), problematic alcohol use (45), cannabis use disorder (CUD) (46), cognitive performance (47), educational attainment (47), household income (48), risky behaviours ( 49) and age at first birth (50).…”
Section: Selection Of Gwas Summary Statisticsmentioning
confidence: 99%
“…As a result, we included summary statistics from GWAS capturing a variety of parental risk factors for conduct problems in the domains of psychiatric conditions, substance use/abuse, cognitive and education-related factors, or other parental risk factors that could underlie potential genetic nurture effects (Table S2). Specifically, we used summary statistics for GWAS on ADHD (40), depression (41), anxiety disorders (42), antisocial behaviour (ASB) (43), lifetime smoking (44), problematic alcohol use (45), cannabis use disorder (CUD) (46), cognitive performance (47), educational attainment (47), household income (48), risky behaviours ( 49) and age at first birth (50).…”
Section: Selection Of Gwas Summary Statisticsmentioning
confidence: 99%
“…The presence of FOXP2 in the large introgression desert on chromosome 7 may have less to do with its well-known role in sensori-motor learning, and more to do with its associations with behavioral traits pertaining to sociability and externalizing behavior (Tielbeek et al, 2022 ; Verweij et al, 2022 ).…”
Section: Signals From Comparative (Paleo)genomicsmentioning
confidence: 99%
“…An extensive body of evidence points to this gene as a critical determinant of antisocial behavior 14 . In addition, a recent meta‐analysis based on genome‐wide association studies (GWAS) in antisocial individuals has shown a significant association between FOXP2 (transcription factor forkhead box protein P2) and antisocial behavior 15 …”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, a recent meta-analysis based on genome-wide association studies (GWAS) in antisocial individuals has shown a significant association between FOXP2 (transcription factor forkhead box protein P2) and antisocial behavior. 15 Several lines of neuroimaging research have shown that the maladaptive social responses in antisocial behavior are contributed by structural and functional deficits of the orbitofrontal cortex (OFC) 16 (for scholarly discussions of the role of the OFC in antisocial behavior, see refs. [17,18]).…”
mentioning
confidence: 99%